Heart Failure in a Young Lady: A Reversible Cause - Ghosh, Kaushik; Sikdar, Sunandan; Ghosh, Susmita; Bhattacharyya, Ambarish; Chakraborty, Sisir; Bag, Arijit (Journal of Diagnostics, 2015)
Finding a reversible cause of pulmonary oedema due to left ventricular dysfunction in intensive care unit is very rare. Here we describe such an event in a young lady who has been diagnosed subsequently as Systemic Lupus Erythromatosus with cardiomyopathy and treated successfully. From ‘Do Not Resuscitate, to ‘doing well’ this is really an encouraging success story.